Molecular Investigation of Curli Fimbriae Genes in Enterobacter cloacae Isolated from Various Clinical Sources in Baghdad, Iraq - Tiba Ayad Ahmed (Journal of Global Pharma Technology, 2018)
Thirteen isolates were collected from various clinical sources during the periodfrom 22/10/2017 to 22/12/2017. All the isolates were diagnosed based on the microscopic and biochemical propertiesby Vitek-2 Compact system. All isolates formed biofilm 100%, with 30% of isolatesbiofilm produced strongly and 70% on medium. The results of the present study have shown the presence of Curli fimbriae genes in E. cloacae bacteria from cases of urinary tract infections, infected patient with blood bacteremia and inflammation of wounds. Curli fimbriae is considered to be an important factor in the virulence of E.cloacae bacteria, which plays an important role in adhering and combining cells on solid surfaces to form the biofilmand helps in the adhesion of bacterial cells. As well as their involvement in the invasion of the host cells, and their interaction with the host proteins and activate it for the host's immune system.